PELAKSANAAN PEMBERIAN HAK-HAK NARAPIDANA PELAKU TINDAK PIDANA PEMBUNUHAN (STUDI DI LEMBAGA PEMASYARAKATAN KLAS II B GUNUNGSITOLI, NIAS) - Fadil Selamat Harefa; Kurnia Konstan Telaumbanua (Jurnal Darma Agung, 2021)
This study aims at finding how the implementation of the granting of rights for murder convicts in Gunung Sitoli Class II B Prison, Nias and the training process at the Gunung Sitoli Class II B Penitentiary, Nias towards murder convicts. Penitentiary as the last place of the criminal correctional system, its task is to carry out the development of prisoners. In carrying out the development of prisoners, the correctional institution is guided by the provisions of Law Number 12 of 1995 concerning Corrections. Prisoners are not people who are excommunicated for actions committed as a result of violating the law. The law regulates the rights of prisoners. The formulation of the problem in this journal is how the implementation of the granting of rights and how the process of coaching the prisoner is. The method used is juridical empirical or juridical empirical research where the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The results of the study concluded that the implementation of granting rights to murder convicts in Gunungsitoli Class II B Penitentiary, Nias was carried out in accordance with the Law. The coaching process starts when the prisoner is detained at the Police, then at the Gunungsitoli Detention Center at the stage of undergoing a trial and continues at the Class II B Prison in Gunung Sitoli, Nias until the prisoner is released.